Field report PAC 671: BoardRoom Business Solutions / Farah Wahida Rozlan - Rozlan, Farah Wahida (Universiti Teknologi MARA, Terengganu, 2024)
BoardRoom began in 1968 as Lim Associates Pte Ltd (LA), offering corporate secretarial and share registration services. Over time, strategic mergers and acquisitions allowed it to expand across the Asia-Pacific region. In 1982, Ee Peng Liang Consultants Pte Ltd (EPLC) was founded, focusing on corporate secretarial and accounting services. In 1986, LA merged with Ernst & Whinney (Singapore) to form Ernst & Young Singapore (EYS), leveraging global resources and expertise for future growth.